Finance for nonfinancial managers - Siciliano, Gene (Briefcase book., 2015)
Financial decisions impact virtually every area of your company. As a manager, it's up to you to understand how and why. This book helps you understand the information in essential financial reports and then shows you how to use that understanding to make informed, intelligent decisions. It provides a solid working knowledge of: basic financial reports; balance sheets, income statements, and cash flow statements; cost accounting; methods to assess which products or services are most profitable to your firm; operational planning and budgeting; and ways to use financial knowledge to strengthen your company. --